2023
DOI: 10.1017/jfm.2023.88
|View full text |Cite
|
Sign up to set email alerts
|

Inertio-capillary rebound of a droplet impacting a fluid bath

Abstract: The rebound of droplets impacting a deep fluid bath is studied both experimentally and theoretically. Millimetric drops are generated using a piezoelectric droplet-on-demand generator and normally impact a bath of the same fluid. Measurements of the droplet trajectory and other rebound metrics are compared directly with the predictions of a linear quasipotential model, as well as fully resolved direct numerical simulations of the unsteady Navier–Stokes equations. Both models resolve the time-dependent bath and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 83 publications
(199 reference statements)
2
10
0
Order By: Relevance
“…This significantly increases computational costs, and the effects of rarefied gas dynamics become significant. To overcome these difficulties, a 2-VOF approach has been proposed and used by several researchers (Ramírez-Soto et al 2020;Alventosa, Cimpeanu & Harris 2023) to study droplet bouncing. By avoiding overlap between the two-volume fraction fields, a situation similar to an incompletely drained air film with a large air film gap can be simulated, ensuring the occurrence of bouncing (see Appendix).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This significantly increases computational costs, and the effects of rarefied gas dynamics become significant. To overcome these difficulties, a 2-VOF approach has been proposed and used by several researchers (Ramírez-Soto et al 2020;Alventosa, Cimpeanu & Harris 2023) to study droplet bouncing. By avoiding overlap between the two-volume fraction fields, a situation similar to an incompletely drained air film with a large air film gap can be simulated, ensuring the occurrence of bouncing (see Appendix).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that bouncing is observed for a certain range of We for equal-size droplet collision in air (Qian & Law 1997). In this study, the ranges of parameters leading to bouncing are selected based on experimental data from studies by Ramírez-Soto et al (2020), Abouelsoud & Bai (2021) and Ray et al (2023a), as well as observations from similar phenomena reported by Qian & Law (1997) and Alventosa et al (2023). The ranges of parameters used in DNS are summarized in table 1.…”
Section: Head-on Bouncing Dynamics Of Unequal-size Dropletsmentioning
confidence: 99%
“…The Basilisk multi-phase flow library has been validated by several recent papers in Journal of Fluid Mechanics , e.g. Mostert, Popinet & Deike (2022) (breaking waves), Alventosa, Cimpeanu & Harris (2023) (droplet impact), Riviére et al. (2021) (turbulent bubble break-up), Mostert & Deike (2020) (dissipation in waves) and Innocenti et al.…”
Section: Methodsmentioning
confidence: 99%
“…2015; Ray, Biswas & Sharma 2015; Deka et al. 2017; Fudge, Cimpeanu & Castrejón-Pita 2021; Alventosa, Cimpeanu & Harris 2023; Fudge et al. 2023) can be found in the literature, focusing on those phenomena that are assumed axisymmetric.…”
Section: Introductionmentioning
confidence: 99%
“…Recent simulations of liquid drops impinging onto liquid surfaces are mostly based on the latter category of models. Substantial axisymmetric simulations of the problem (Morton et al 2000;Josserand & Zaleski 2003;Berberović et al 2009;Thoraval et al 2012;Ervik et al 2014;Agbaglah et al 2015;Ray, Biswas & Sharma 2015;Deka et al 2017;Fudge, Cimpeanu & Castrejón-Pita 2021;Alventosa, Cimpeanu & Harris 2023;Fudge et al 2023) can be found in the literature, focusing on those phenomena that are assumed axisymmetric. For three-dimensional (3-D) calculations, whose primary objective is to capture the non-axisymmetric mechanisms involved in the splashing process, efforts were focused on dynamic refinement techniques (Popinet 2003;Nikolopoulos, Theodorakakos & Bergeles 2007), in order to resolve multiple interfaces resulting from the splash, while ensuring a reasonable grid size.…”
Section: Introductionmentioning
confidence: 99%